2015
DOI: 10.1002/chem.201501615
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and Cationic Molybdenum Imido Alkylidene N‐Heterocyclic Carbene Complexes: Reactivity in Selected Olefin Metathesis Reactions and Immobilization on Silica

Abstract: The synthesis and single-crystal X-ray structures of the novel molybdenum imido alkylidene N-heterocyclic carbene complexes [Mo(N-2,6-Me2C6H3)(IMesH2)(CHCMe2Ph)(OTf)2] (3), [Mo(N-2,6-Me2C6H3)(IMes)(CHCMe2Ph)(OTf)2] (4), [Mo(N-2,6-Me2C6H3)(IMesH2)(CHCMe2Ph)(OTf){OCH(CF3)2}] (5), [Mo(N-2,6-Me2C6H3)(CH3CN)(IMesH2)(CHCMe2Ph)(OTf)](+)BArF(-) (6), [Mo(N-2,6-Cl2C6H3)(IMesH2)(CHCMe3)(OTf)2] (7) and [Mo(N-2,6-Cl2C6H3)(IMes)(CHCMe3)(OTf)2] (8) are reported (IMesH2=1,3-dimesitylimidazolidin-2-ylidene, IMes=1,3-dimesityli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 64 publications
8
88
1
Order By: Relevance
“…We already have shown that cationic molybdenum imido alkylidene NHC complexes are highly active catalysts in various olefin metathesis reactions . Here we prepared a wide range of complexes with the general formula [Mo( N R′)(CHCMe 2 R)(NHC)(X)][B(Ar F ) 4 ] (Figure , X=anionic ligand).…”
Section: Resultsmentioning
confidence: 99%
“…We already have shown that cationic molybdenum imido alkylidene NHC complexes are highly active catalysts in various olefin metathesis reactions . Here we prepared a wide range of complexes with the general formula [Mo( N R′)(CHCMe 2 R)(NHC)(X)][B(Ar F ) 4 ] (Figure , X=anionic ligand).…”
Section: Resultsmentioning
confidence: 99%
“…Both catalysts tolerate ethers, thioethers, and esters under biphasic reaction conditions. Finally, a comparison with the reactivity of a silica‐supported version, [Mo{ N ‐2,6‐(Me 2 )C 6 H 3 }(CHCMe 2 Ph)(2‐{silica‐ O ‐methylene}‐imidazolin‐2‐ylidene)](OTf) 2 ( I 2 ) revealed superior activity of both 3 and 5 . Compared to a silica‐based version of a tungsten oxo alkylidene NHC catalyst, [(≡SiO)W(=O)(=CHCMe 2 Ph)(IMes)][B(Ar F ) 4 ], again similar activity was observed, at least for diallyl ether and diallyl diphenylsilane.…”
Section: Resultsmentioning
confidence: 99%
“…Its formation is proposed to be a result of the smaller buried volume for Mo‐1 compared Mo‐4 , resulting in easier access of substrates to the metal core. Thus, cation formation is believed to occur simultaneously with substrate (or CD 3 CN) coordination, similar to the formation of cationic species in Mo and W imido/oxo‐alkylidene NHC complexes . With this mechanistic understanding at hand, the slower reactions rates of Mo‐1 – Mo‐4 compared to complex I are comprehensible, because tetracoordinated species I requires no dissociation of the NHC or an alkoxide ligand.…”
Section: Figurementioning
confidence: 96%